A homozygote for pericentric inversion of chromosome 4. Issue 6 (December 1982) - Carpenter, N J; Say, B; Barber, N D
Abstract : A child with developmental and language delay was found to be homozygous for a pericentric inversion of chromosome 4 (inv(4) (p15 X 2q12)). Her normal mother and aunt are inversion heterozygotes. It is suggested that the phenotypic abnormalities may have resulted from damage at chromosomal breakpoints or from a position effect which is expressed only in homozygous form.